From Night kitchen to Wolves in the walls: a brief psychoanalytic look at children's picture books. Issue 2 (3rd May 2016) - Zuppardi, Sam
Abstract : This article uses psychoanalytic theory to look at a range of contemporary picture books, and argues that picture books allow child readers an opportunity to engage with their own primitive anxieties. It begins with a brief look at the history of children's literature, arguing that the genre has developed to allow for increasingly complex representations of children's internal worlds. Alongside this, it considers the value and application of psychoanalytic theory to literary criticism in order to contextualise its own approach to the books it later looks at. The article focuses in on picture books as a specific genre within children's literature and uses Maurice Sendak's picture book In the night kitchen to outline some of the key characteristics that make picture books especially suited to the articulation of primitive anxieties in ways that child readers can engage with and take ownership of. The second part of the article examines a number of contemporary picture books, analysing them in terms of their unconscious content in order to demonstrate the ways in which psychoanalytic ideas can be usefully applied to such texts.